2014
DOI: 10.1097/md.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Infection in Hemodialysis and Other Vascular Grafts

Abstract: Prosthetic arteriovenous (AV) graft infection is the principal cause of morbidity related to chronic hemodialysis AV graft fistula. Coxiella burnetii is a known pathogen that causes fever, pneumonia, and intravascular infections with the limitation of negative cultures. Herein, we report the first case of a patient who presented to the emergency department of our hospital with a prosthetic hemodialysis AV graft infection due to Coxiella burnetii. We also performed a literature search with PubMed to identify st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Coxiella burnetii ( C . burnetii ) is the etiologic agent of Q fever, a known pathogen that causes fever, pneumonia, and intravascular infections [ 5 , 6 ]. Studies of CAP have traditionally focused little on viral causes[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coxiella burnetii ( C . burnetii ) is the etiologic agent of Q fever, a known pathogen that causes fever, pneumonia, and intravascular infections [ 5 , 6 ]. Studies of CAP have traditionally focused little on viral causes[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, viral infections are also involved with 80% of episodes of CAP in children under 2 years old and over 40% of older children [ 6 11 ]. The existing studies have showed that respiratory syncytial virus (RSV) and influenza viruses (Flu) are important pathogens among the hospitalized and outpatient children presenting with ARTI [ 5 , 6 ].Adenovirus virus (ADV) and parainfluenza viruses (PIV) are also associated with a substantial proportion of ALRI in infants and young children [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Hagenaars et al, PET-scan has a positive predictive value of 78% and a negative predictive value of 77% for the diagnosis of Q fever vascular infections [31]. In a retrospective study involving 167 patients with active C. burnetii infection, 18 F-FDG PET/CT changed the diagnosis for 62.6% of patients and revealed a previously unsuspected focus of infection in 38.7% of cases. This innovation was a strong argument for a paradigm change from chronic Q fever to C. burnetii persistent focalized infection.…”
Section: Discussionmentioning
confidence: 99%